Patterns of primary glomerular diseases among adults in the western region of Saudi Arabia - Jalalah Sawsan (Saudi Journal of Kidney Diseases and Transplantation, 2009)
The frequency of primary glomerular diseases is variable from one part of the world to the other. Data published from Saudi Arabia has shown wide range of variation in the different regions of the country. This study reports the frequency of primary glomerulonephritis (GN) in adults in the Western region of Saudi Arabia. The study is based on retrospective evalua-tion of archived renal biopsy in the period of 18 years (1989-2007). The 296 selected cases of primary GN were studied by light, immunofluorescence, and electron microscopy. The patients age range between 17-76 years. Results show that the most frequent primary GN is membranous GN (MGN) constituting 25.7%, followed by focal segmental glomerulosclerosis (FSGSC) at 21.3%. Less frequent GN are immunoglobulins A nephropathy (IgAN) representing 17.6%, membrano-proliferative GN (MPGN) 11.5%, immunoglobulin M nephropathy (IgMN) 7.8%, minimal change disease (MCD) 5.4% and mesangioprolifertive GN (MesPGN) 4.7%. Other GN which are rarely encountered in this study are fibrillary GN (FGN) (3%), postinfectious GN (PIGN) (2%), Alport syndrome (AS) (0.7%) and membranoproliferative GN type II or dense deposit disease (DDD) (0.3%). In conclusion this study demonstrates that MGN is the most common primary GN encountered in the studied cases, the second more frequent is FSGSC. This result is in contrast to previous reports from Saudi Arabia where MGN is reported with low frequency and FSGSC is reported the most common primary GN.